A política de responsabilidade social da empresa Furnas - São José da Barra - Queiroz, Adriana de Souza Lima [UNESP] (2014)
This paper discusses corporate social responsibility with the aim of knowing and systematize social responsibility held in a large company in the electric sector - Furnas Power Plant located in São José da Barra/MG to then understand the commitment with its social responsibility policy. The research was conducted through literature review, document analysis and field research, in order to ascertain the historical process of social responsibility and its motion provides legitimacy in their actions, also inserting their key actors such as firms, State and Civil Society. And finally, listing some behavioral categories of social responsibility. For systematization of social responsibility in Furnas Power Plant we uses data in the public domain as the social balance (IBASE), the social sustainability report released by the company and interviews with people involved in corporate social responsibility. As a result we sought to build articulate reflections that theoretical interpretation with the knowledge constructed in research, understanding that have social responsibility programs or a policy of social responsibility is not to say that in fact the company is committed to social responsibility practices